Explorasi Dimensi dan Pengukuran Intellectual Capital: Pendekatan Sistematik Literature Review - Yuki Fitria; Perengki Susanto; Yunia Wardi; Susi Evanita; Hendrik Heri Sandi (Jurnal Ecogen, 2025)
The presence of SMEs plays a crucial role in a country, as it demonstrates how entrepreneurship contributes to improved economic growth.Globalization has led to increasingly fierce business competition, requiring business actors to continue to innovate. However, in reality, the ability to innovate and competitiveness are major weaknesses for most SMEs, including those in Padang City. Therefore, business actors should apply intellectual capital. The application of intellectual capital can enhance competitive advantage through the creation of more innovative products, thereby positively impacting SMEs performance. The approach employed in this research is a Systematic Literature Review (SLR), focusing on articles published between 2020 and 2025. These articles were sourced from prominent online academic databases and accessed through the website https://www.sciencedirect.com/. Based on a thorough review of twenty-five articles in the database, it was found that the majority of researchers, 21 articles, identified three dimensions of intellectual capital: human capital, relational/customer capital, and structural capital. This finding aligns with the study by Sulastri, et al (2020), who also developed dimensions that can effectively measure intellectual capital in SME-scale companies, particularly in the city of Padang. In total, there are 22 statements that can be used to assess the intellectual capital of SME-scale companies.